A review of the genus Orthotylus Fieber (Heteroptera: Miridae: Orthotylinae) in Korea, with a discussion on geographical variation and distributional records of O. salicis and O. riparius - Oh, Minsuk; Kim, Wonwoong; Lee, Seunghwan (Zootaxa, 2022)
The plant but genus Orthotylus Fieber, 1858 in Korea is reviewed. One species, O. riparius Kulik is newly recorded from the Korean peninsula. Diagnostic characters of each species are discussed, with the images of adult specimen and genitalic structures. Additionally, a key to the Korean Orthotylus species is presented. Chinese record of O. riparius is excluded based on critical literature reviews. Observed variant of O. riparius Kulik and O. salicis Jakovlev are discussed.